2019
DOI: 10.1021/acsomega.8b03414
|View full text |Cite
|
Sign up to set email alerts
|

Dual Stimuli-Responsive Block Copolymers for Controlled Release Triggered by Upconversion Luminescence or Temperature Variation

Abstract: An amphiphilic block copolymer (BCP) which contains both photoresponsive and thermoresponsive blocks was synthesized by the atom transfer radical polymerization approach. Meanwhile, a new core/shell type of the upconversion nanoparticle (UCNP) LiYF 4 :Yb 3+ 0.25 ,Tm 3+ 0.01 @LiYF 4 :Yb 3+ 0.2 was successfully synthesized. By encapsulating UCNPs inside the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Nanoparticles of LiYF 4 doped with Yb 3+ , Er 3+ , Ho 3+ , and Tm 3+ ions were synthesized by the thermal decomposition of the lanthanide and lithium triuoroacetate precursors in the presence of oleic acid coordinating ligands and noncoordinating 1octadecene solvent molecules, according to our previously reported procedure. [18][19][20] Briey, a batch of Yb 3+ -, Er 3+ -, Ho 3+ -, and Tm 3+ -doped LiYF 4 (74 mol% Y, 20 mol% Yb, 2 mol% Er, 2 mol% Ho, and 2 mol% Tm) was obtained as follows: Li 2 CO 3 (1.48 mmol), Y 2 O 3 (0.74 mmol), Yb 2 O 3 (0.2 mmol), Er 2 O 3 (0.02 mmol), Ho 2 O 3 (0.02 mmol), and Tm 2 O 3 (0.02 mmol) were dissolved in 50% triuoroacetic acid (TFA) at 80 C in a three-necked ask. Then, the solutions were evaporated to dryness under an argon gas purge.…”
Section: Synthesis Of Ucnpsmentioning
confidence: 99%
“…Nanoparticles of LiYF 4 doped with Yb 3+ , Er 3+ , Ho 3+ , and Tm 3+ ions were synthesized by the thermal decomposition of the lanthanide and lithium triuoroacetate precursors in the presence of oleic acid coordinating ligands and noncoordinating 1octadecene solvent molecules, according to our previously reported procedure. [18][19][20] Briey, a batch of Yb 3+ -, Er 3+ -, Ho 3+ -, and Tm 3+ -doped LiYF 4 (74 mol% Y, 20 mol% Yb, 2 mol% Er, 2 mol% Ho, and 2 mol% Tm) was obtained as follows: Li 2 CO 3 (1.48 mmol), Y 2 O 3 (0.74 mmol), Yb 2 O 3 (0.2 mmol), Er 2 O 3 (0.02 mmol), Ho 2 O 3 (0.02 mmol), and Tm 2 O 3 (0.02 mmol) were dissolved in 50% triuoroacetic acid (TFA) at 80 C in a three-necked ask. Then, the solutions were evaporated to dryness under an argon gas purge.…”
Section: Synthesis Of Ucnpsmentioning
confidence: 99%
“…This is usually done in high boiling oleic acid-based solvent mixtures, similar to the synthesis of NaYF4 upconversion nanocrystals [62][63][64][65][66]. Since the particles have a small size and display a relatively strong luminescence, they have been proposed for a variety of biomedical and bioimaging applications [79,80,83,87], as well as for transparent displays [70,74] and chemosensing [86]. Due to their large surfaceto-volume ratio, however, surface quenching of the luminescence presents a severe problem, often reducing the photoluminescence quantum yield of the nanocrystals by several orders of magnitude compared to the bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…Core particle synthesisHOA-based synthesis procedures for nanocrystalline LiYF4 are usually based on the thermal decomposition of trifluoro acetates[63,64,66,67,[78][79][80][81][82][83][84][85][86][87][88][89] or on the reaction of yttrium oleate with either ammonium fluoride and lithium oleate[77] or ammonium fluoride and lithium hydroxide[62,65,[68][69][70][71][72][73][74][75][76]. Here, we prepared the LiYF4 nanoparticles at temperatures above 200 °C via the reaction of ammonium fluoride with rare earth oleates and lithium oleate dissolved in oleic acid/octadecene[62,65,[68][69][70][71][72][73][74][75][76][77].…”
mentioning
confidence: 99%
“…More importantly, to synthesize a kind of UCNPs that can emit UV light and can be applied as a trigger for photoresponsive materials, some preliminary experiments were conducted. As our previous study indicated that UV-emissive LiYF 4 -type UCNPs can be obtained by the single doping of Tm 3+ [ 38 , 44 ], we optimized the doping concentrations of Yb 3+ and Tm 3+ to synthesize LaF 3 UCNPs with luminescence characteristics in the UV region. As the UC emission is strongly related to the cross-relaxation of the doping ions, we increased the concentration of Yb 3+ (sensitizer) and decreased the concentration of Tm 3+ (activator) based on the doping concentrations shown in Figure 5 b.…”
Section: Resultsmentioning
confidence: 99%